2018
DOI: 10.1371/journal.pone.0204558
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of common mental disorders among dental students in Brazil

Abstract: This study aimed to estimate prevalence of common mental disorders (CMD) and associated factors among dental students. In this cross-sectional study, 230 students answered a questionnaire and instruments to assess CMD (Self Reporting Questionnaire-20), hazardous alcohol consumption (Alcohol Use Disorder Identification Test), social support (Social Support Scale), perceptions of academic life (Dundee Ready Education Environment Measure), coping (Ways of Coping Inventory) and resilience (Resilience Scale). Bivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 73 publications
(101 reference statements)
2
17
0
7
Order By: Relevance
“…Understanding the factors that are detrimental to, or protective of, students’ mental health can help educators combat issues and create a dental school environment where students can thrive academically and socially. This study's finding of resilience as a protective factor provides further context for the importance of better understanding resilience in dental students . A study of the impact of learning environment disruption on dental student learning experiences, found that a high value on people facilitated a greater resilience .…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Understanding the factors that are detrimental to, or protective of, students’ mental health can help educators combat issues and create a dental school environment where students can thrive academically and socially. This study's finding of resilience as a protective factor provides further context for the importance of better understanding resilience in dental students . A study of the impact of learning environment disruption on dental student learning experiences, found that a high value on people facilitated a greater resilience .…”
Section: Introductionmentioning
confidence: 67%
“…It has been previously documented that resilient individuals were more achievement‐oriented, pursued more education, and almost all held full‐time jobs in their adult life . Their adult career success, despite social adversities, was related to their strong ability to plan and organize, denoted as “planfulness.”…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 13 articles were further excluded due to the differences in the study population and study settings. Among these, six were conducted in Saudi Arabia [21,22], Pakistan [23], Brazil [24], Egypt [25], and Somalia [26]. The other six studies were excluded because of their different study population (conducted other than college/university students) [27][28][29][30][31][32].…”
Section: Search Resultsmentioning
confidence: 99%
“…Students who reported a change in their career plans also had lower resilience scores compared to those who did not report a change in their plans, corroborating prior evidence that resilience is a key psychological resource that could make career shocks more manageable ( Akkermans et al 2020 ). Resilient individuals show career success, despite adversities, due to their strong ability to plan and organize, often denoted as “planfulness” ( Graner et al 2018 ). Given these findings, academic dental institutions need to prioritize the creation of responsive academic environments that not only best prepare students for their future careers but also address concerns related to their well-being.…”
Section: Discussionmentioning
confidence: 99%